Influencia del gasto público en la calidad educativa básica regular en las regiones: Arequipa, Cusco, Junín, La Libertad y Piura para el periodo 2007 - 2016 - Zavaleta Jara, Mary Carmen (2018)
The main objective of this research work is to determine the influence of public spending on the regular basic educational quality in the regions: Arequipa, Cusco, Junín, La Libertad and Piura; Period 2007 - 2016. For this purpose, an analysis of public expenditure was carried out, whose indicators are: Schools that have access to the Internet, Public premises connected to the electricity network, Public premises connected to a drinking water network, Public premises connected to the drainage network; and if these variables positively influence the regular basic educational quality defined as: Academic achievement of students in reading comprehension and in mathematics. The methodology used in this research is based on the analysis of the current reality of Regular Basic Education using statistical data from five regions of Peru for a period of ten years, for which the linearized Cobb-Douglas production function was used by means of a econometric data model panel using the econometric E-Views program. To arrive at the results, three possible forms of regression were carried out: Panel with fixed effects of crossed sections, Panel with fixed time effects and Panel with fixed effects of cross sections and time, applying these regressions it was decided to exclude two indicators: Public premises connected to the electricity network and to the drainage network, given that the first was not significant and the other did not comply with the expected sign, once excluded, the cross-section fixed effects panel was chosen, which presented better significance. It was observed that throughout the 2007-2016 study period, Public Expenditure has significantly influenced the primary regular basic educational quality.